Observations of spatial and physical characteristics in the public space environment as a measurement parameter of visual comfort - Ghoustanjiwani Adi Putra; Daim Tri Wahyono (ESE International Journal (Environmental Science and Engineering), 2020)
This descriptive qualitative study is part of the prelimanary study which aims to examines of spatial and physical characteristics in the public space environment as a measurement parameter of visual comfort on the quality of the environment public open space. The author will conduct a qualitative descriptive analysis using literature data and results of previous studies in evaluating the quality of public spaces based on visual quality. This case study takes an object in the form of green open space, "Singha Park," with all the forming attributes in the form of hardscape and softscape elements. In this study, it was found that "Taman Singha" is a reasonably effective and in good quality. Based on the analysis and observations on visual physical characters using guidelines from PPS (Project of Public Space), 2011. Using six PPS parameters, we found that using two parameters of visual quality measurement, namely: Comfort and image. where these two parameters are found in "Taman Singha."